Effect of cattle age on the physio-chemical properties of beef - Liza , FA; Hosssan, MI; Hashem , MA; Rahman , MM (Meat Research, 2024)
This study, conducted at Bangladesh Agricultural University, examined how the age of indigenous cattle affects beef quality, focusing on the Longissimus dorsi muscle. The cattle were divided into three age groups: 1.5 years, 2 years, and 2.5 years. Various physical and chemical properties of the meat were analyzed, including pH levels, drip loss, tenderness, cooking loss, water holding capacity (WHC), and chemical composition. The study found that pH levels measured at both 0- and 24-hours post-slaughter showed no significant differences between age groups, and all values were within the normal range, indicating that pH did not impact meat quality. However, drip loss was significantly higher in the 2.5-year-old cattle (3.15%), suggesting that older cattle lose more water from their muscle fibers, which could affect meat texture and juiciness. In terms of tenderness, measured by shear force, the 2.5-year-old cattle were the toughest (52.5 N), while the 1.5-year-olds were the most tender (38.86 N). The 2-year-old cattle were in between. The tenderness improved for the 1.5-year-olds after 24 hours, while the 2.5-year-olds maintained their tougher texture. The 2.5-year-old cattle also had higher cooking loss, meaning they lost more moisture during cooking, which could result in less juicy meat. In contrast, the 1.5-year-old cattle had lower cooking loss, aligning with consumer preferences for more tender and juicy beef. The 1.5-year-olds also exhibited higher WHC (5.64%), which likely contributed to their superior tenderness and juiciness. Chemical analysis revealed that the 1.5-year-olds had the highest moisture content (75.89%), while the 2.5-year-olds had higher protein (22.37%) and ash content, reflecting a more developed muscle structure.